Systematic review of adverse health outcomes associated with high serum or red blood cell folate concentrations - Colapinto, Cynthia K. (J Public Health (Oxf), 2016)
BACKGROUND: To examine the relationship between reported high serum or red blood cell (RBC) folate status and adverse health outcomes. METHODS: We systematically searched PubMed/Medline and EMBASE (to May 2013), with no limits by study type, country or population, to identify studies reporting high folate concentrations in association with adverse health outcomes. Two reviewers screened studies and extracted data. Study quality was assessed. RESULTS: We included 51 articles, representing 46 studies and 71 847 participants. Quantiles were used by 96% of studies to identify high folate concentrations. Eighty-three percent of serum folate and 50% of RBC folate studies reported a high folate cutoff that corresponded with a clinically normal concentration. Increasing values of reported high folate concentration did not demonstrate a consistent association with risk of adverse health outcomes. Overall, reported high folate concentrations appeared to be associated with a decreased risk of adverse health outcomes, though substantial methodological heterogeneity precluded complex analyses. CONCLUSIONS: Our interpretation was complicated by methodological variability. High folate cutoffs varied and often corresponded with normal or desirable blood concentrations. In general, a negative association appeared to exist between reported high folate status and adverse health outcomes. Consistent methods and definitions are needed to examine high folate status and ultimately inform public health interventions.